2023
DOI: 10.21608/svuijas.2023.200741.1279
|View full text |Cite
|
Sign up to set email alerts
|

Red beetroots - a potential dietary supplement in the management of hypercholesterolemia

Abstract: Red beetroot juice was studied for its potential antihypercholesterolemic effects in cholesterol-rich diet-induced hypercholesterolemia. Thirty healthy adult albino rats were freely divided into two major groups, the first of which was fed on a baseline diet only (control negative: 6 rats), and the second of which was provided a hypercholesterolemic diet (24 rats) for 4 weeks. Chemical composition of red beetroots (ash, crude fats, crude proteins, crude fiber, carbohydrates, phenolic and flavonoids compounds) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…Moisture and total ash contents found to be 86.1% and 0.5%, respectively. Moftah et al (2023) reported the same results for moisture, carbohydrate and total protein contents expect the total fiber content that was significantly lower (1.9%). Bangar et al (2022) registered that the ash and total fiber of red beet root were 1.08% and 2.8%, respectively.…”
Section: Gross Chemical Analysis Of Red Beet Rootsupporting
confidence: 64%
“…Moisture and total ash contents found to be 86.1% and 0.5%, respectively. Moftah et al (2023) reported the same results for moisture, carbohydrate and total protein contents expect the total fiber content that was significantly lower (1.9%). Bangar et al (2022) registered that the ash and total fiber of red beet root were 1.08% and 2.8%, respectively.…”
Section: Gross Chemical Analysis Of Red Beet Rootsupporting
confidence: 64%